Functional and health-endorsing properties of wheat and barley cell wall's non-starch polysaccharides. Issue 1 (1st January 2018) - Bader Ul Ain, Huma; Saeed, Farhan; Ahmad, Nazir; Imran, Ali; Niaz, Bushra; Afzaal, Muhammad; Imran, Muhammad; Tufail, Tabussam; Javed, Ahsan
ABSTRACT: Cereals have captured global importance owing to the presence of bioactive moieties in cell wall. Numerous components have been considered but non-starch polysaccharides (NSP) of cereals cell wall are of prime concern. In this comprehensive review, the basic aim is to elaborate the functional and nutritional importance of cereals cell wall with special reference to NSP. Among bioactive components of cell wall, NSP, such as arabinoxylans, ß-glucans, and arabinogalactans of wheat and barley, have gained much importance. Moreover, literature revealed that NSP have greater role as prebiotic, immunomodulator, antioxidant, anti-diabetic, and cardio-protector as well as major food applications.